Social management and quality of life: review of theoretical currents - Márquez Bravo, Yessenia Johana (2024)
The objective of this research is to analyze the conceptual foundations and theoretical currents that frame the relationship between the social variable management and quality of life with the purpose of framing their relationship and conceptualization. The type of research used is bibliographic - descriptive, since a general search was carried out in different databases such as Redalyc; Dialnet; Academic google; Jstor; SciELO; Scopus; Dimensions and La Reference., using search criteria according to each variable, and subsequently executing a coding through the use of Atlas Ti., as an information synthesis tool. Articles published in different languages ​​were consulted, and the pertinent information was synthesized from them through the diagramming of codes and networks. As a conclusion of the research process, social management is considered as a fairly broad field of various theoretical criteria according to the area of ​​applicability, while quality of life refers to the level of satisfaction that individuals have according to a group of indicators. personal and work-related events that mark their daily lives.